STEERING ACCURACY AND SITTING SYMMETRY DURING SIMULATED DRIVING IN DRIVERS WITH CHRONIC STROKE - Shin, Hwa-Kyung; Ryu, Young Uk; Lee, Ho-Cheol (International Journal of Psychosocial Rehabilitation, 2020)
The steering while sitting in the driver’s seat is one of the most basic and important driving performance. The purpose of this study was to investigate the characteristics of sitting symmetry and steering accuracy of stroke drivers compared to healthy drivers, and to examine the correlation between them.Fifteen stroke drivers and fifteen healthy drivers participated in this study. Both group performed the large and small s-curve driving during five minute. Accuracy index (AI) was measured by comparing the performance line that drove along large s-curve and small s-curve (target line). Symmetry index (SI) was calculated by difference of right and left seat pressure. The steering AI of stroke drivers was significantly lower than that of healthy adult drivers (p <0.05), and the AI of small S-curves was significantly lower than that of large S-curves (p <0.05). The sitting SI of stroke drivers was significantly greater than that of healthy driver (p <0.05). Also, AI of stroke driver showed significant correlation with SI in both S-curve. However, healthy drivers had no significant correlation between SI and AI (p> 0.05). SI and AI are valid variables for evaluating the stroke driver’s driving ability in off-road environment.